IDENTIFYING FACTORS OF CONSUMER’S PURCHASE INTENTION ON E-CARS - Maulida, Dhita Nur; Amalia, Fatya Alty (UI Scholars Hub, 2024)
Manuscript type: Research Article Research Aims: To evaluate the factors that can shape attitudes to use and purchase intentions for e-cars, either directly or through mediating variables. Design/methodology/approach: Data were collected through a quantitative approach by administering a survey to 410 respondents, both those who already owned an e-cars and those who did not. Analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Research Findings: The output shows that Performance Expectancy and Social Influence significantly influence Attitude Toward Using and Purchase Intention. Meanwhile, Facilitating Condition positively affects Attitude Toward Using, but requires the mediation of Attitude Toward Using to have a positively impact on Purchase Intention. In contrast, Effort Expectancy, Price Value, and Perceived Risk show insignificant influence on Attitude Toward Using and Purchase Intention. Theoretical Contribution/Originality: This study applies modifications to the UTAUT-2 model by adding Perceived of Risk to expand understanding of the personal aspects of consumers that can influence the formation of usage attitudes and increase purchase intentions for e-cars. Practitioner/Policy Implication: In addition to focusing on the performance of e-cars products, manufacturers must be effective in communicating product benefits to consumers to form positive attitudes. This can be done through careful marketing communication strategies and comprehensive branding efforts, including the utilization of social media to increase brand exposure and convey the benefits of e-cars clearly and effectively. Research limitation/Implications: Geography, the majority of respondents own conventional cars, and the focus of this research is only on e-cars.